2004
DOI: 10.1093/gerona/59.8.b789
|View full text |Cite
|
Sign up to set email alerts
|

How Much Should We Eat? The Association Between Energy Intake and Mortality in a 36-Year Follow-Up Study of Japanese-American Men

Abstract: Energy restriction extends life span and lowers mortality from age-related diseases in many species, but the effects in humans are unknown. We prospectively examined this relationship in a large epidemiological study of Japanese-American men. We followed 1915 healthy nonsmokers, aged 45-68 years at study onset, for 36 years. Twenty-four-hour recall of diet was recorded at baseline, and follow-up was for all-cause mortality. After adjustment for age and other confounders, there was a trend toward lower mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 39 publications
2
41
0
1
Order By: Relevance
“…For example, a study that tracked 1915 healthy men aged 45-68 for 36 years found that all-cause mortality declined with decreasing caloric intake (Willcox et al 2004). These findings held true down to 50% of the group mean energy intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study that tracked 1915 healthy men aged 45-68 for 36 years found that all-cause mortality declined with decreasing caloric intake (Willcox et al 2004). These findings held true down to 50% of the group mean energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Below 50%, mortality started increasing. Likewise, Okinawans consume about 17% fewer calories than the mainland Japanese people and have 40% lower risk of cancer and cardiovascular disease (Willcox et al 2004). Moreover, Okinawans, as opposed to mainland Japanese people, are also significantly shorter and have longer life expectancies.…”
Section: Discussionmentioning
confidence: 99%
“…About 25 distinct biological factors have been identified (11,13,14,16,19) that support the benefits of smaller human body size in terms of health and longevity. For example, when compared to taller people of the same body proportions, shorter people have lower blood pressure, lower left ventricular mass, lower DNA damage, lower C-reactive protein, and lower insulin and insulin like growth factor-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, many researchers attribute our increasing health problems to the high meat and calorie diet of the industrialized world. It is interesting that a Hawaiian study (19) of elderly men found a progressive decrease in mortality with decreasing caloric intake down to 975 kcal. (This practice requires a low calorie but highly nutritious diet and should be implemented under medical supervision).…”
Section: Discussionmentioning
confidence: 99%
“…DPK yang melibatkan pengurangan 15 sehingga 40% penggunaan tenaga seharian merupakan kaedah pengurangan pengambilan kalori tanpa menyebabkan malnutrisi dan pengurangan pengambilan nutrien yang diperlukan oleh badan (Masoro 2005;Varady 2011). Namun demikian, bagi mengelakkan manultrisi semasa mengamalkan DPK, seseorang individu itu harus mempunyai pengetahuan dan pemahaman dalam nutrisi dan juga dipantau oleh pengamal perubatan yang kompeten (Willcox et al 2004). Hal ini bagi mengelakkan kemudaratan ke atas badan apabila kekurangan kalori yang keterlaluan.…”
Section: Pendahuluanunclassified